Incidence of aminoglycoside-induced hearing loss in HIV positive and HIV negative multidrug-resistant tuberculosis patients - Harris, Tashneem (Division of Otorhinolaryngology, 2014)
Aims of the study: To document the incidence and severity of aminoglycoside-induced ototoxicity at Brooklyn Chest Hospital; To determine the prevalence of the 6 known aminoglycoside-induced deafness mutations in the MT-RNR1 gene (A1555G, C1494T, T1095C, T1291C, A827G and 961 indel C) in a cohort of MDR-TB patients; To determine whether HIV positive MDR-TB patients are more likely to develop aminoglycoside-induced hearing loss than HIV negative MDR-TB patients; To provide clinical guidelines to the medical fraternity on the use of aminoglycoside antibiotics with regard to the side-effect of ototoxicity.